2021
DOI: 10.1039/d0fo02491k
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based quantitative proteomic analysis of the antimicrobial mechanism of lactobionic acid againstStaphylococcus aureus

Abstract: The ultrastructural of Staphylococcus aureus cells was changed after treating with lactobionic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In this case, the possible disruptive effect of the LBA on the cell wall membrane was suggested by the presence of alkaline phosphatase and nucleotides in the culture medium and by the transmission electron microscopy (TEM) observations. In a further study, Cao and Zheng 17 provided a deeper insight into this subject by carrying out an iTRAQ‐based quantitative proteomic analysis, which suggested that the LBA was affecting the expression of ABC transporters, altering the cellular metabolism, and decreasing the levels of proteins involved in the survival of the bacteria under stress conditions. Likewise, LBA could attenuate the virulence of Staphylococcus aureus and reduce its capacity of infection.…”
Section: Antimicrobial Properties In Foodmentioning
confidence: 99%
“…In this case, the possible disruptive effect of the LBA on the cell wall membrane was suggested by the presence of alkaline phosphatase and nucleotides in the culture medium and by the transmission electron microscopy (TEM) observations. In a further study, Cao and Zheng 17 provided a deeper insight into this subject by carrying out an iTRAQ‐based quantitative proteomic analysis, which suggested that the LBA was affecting the expression of ABC transporters, altering the cellular metabolism, and decreasing the levels of proteins involved in the survival of the bacteria under stress conditions. Likewise, LBA could attenuate the virulence of Staphylococcus aureus and reduce its capacity of infection.…”
Section: Antimicrobial Properties In Foodmentioning
confidence: 99%
“…Proteomics and metabolomics are effective approaches to investigate the changes of proteins and metabolic profiles in bacteria caused by environmental stress, and which have been extensively used to elucidate the antimicrobial mechanism of natural compounds. 8,19,20 In this study, the minimum inhibitory concentration (MIC) value, intracellular ATP concentration, membrane permeability, and ultrastructure changes were determined to assess the antibacterial effect of hexanal against V. parahaemolyticus. TMT-based quantitative proteomics and non-targeted metabolomics were performed to reveal the associated mode of action of hexanal against V. parahaemolyticus.…”
Section: Introductionmentioning
confidence: 99%